Sweden now 1977-II - Testologen Ltd. (IMU-Testologen AB, 1983)
In the middle of the sixties Testologen AB, in cooperation with a group of advertisers, introduced a new way of investigation where data about the target groups, i.e. interests, consumer habits, possessions, buying intentions, and data about reading habits were collected in the same survey. At SSD there are now surveys available from the Sweden Now series covering the period 1972-1991.
In the 1977 survey the respondents had to indicate their reading habits concerning fifteen different daily papers, weekdays and weekends respectively. They also had to state their reading habits concerning nearly fifty papers from the weekly and monthly press. Other questions dealt with the household´s possession of a number of capital goods such as, car, camera, projector, washing machine, dishwasher, etc. and also if there were any dogs, cats, aquarium fishes or cagebirds in the household. A group of questions is dealing with buying habits and purchasing intentions for a number of products, as well as how frequently different shops are visited. A number of questions about personal interests are introduced by ´Human interests are different. How great is your interest for the following subjects and activities´. Subsequently the respondent is asked how interested he/she is in buying food, cooking, having guests, leisure time activities, etc. There is information about the respondent´s gender, marital status, age, income, occupation, education and housing, and also about the household´s size, age structure, and total income of household. Sweden Now 1977 is almost a total replication from the year before. The only exception is that a group of questions about decisional power in the household have been added.

Purpose:

Collect broad information about interests, purchasing habits and media choices

I mitten av 1960-talet introducerade Testologen AB, i samverkan med en grupp annonsörer, en ny undersökningsform som innebar att målgruppsdata - socio-ekonomiska data, intressen, köpvanor, innehav, köpavsikter mm - och läsvanedata insamlades i en och samma undersökning. Undersökningarna går under benämningen 'Sverige Nu', men databanken marknadsförs under benämningen ORVESTO. Namnet ORVESTO markerar målsättningen att täcka många mediagrupper: OR som i organisationspress, VE som i veckopress och STO som i storstadspress. Vid SND finns ORVESTO-undersökningar som täcker en tjugoårsperiod, 1979-1991 tillgängliga.

Syfte:

Samla in en bred information om intressen, köpvanor och mediaval
ORVESTO 1977-II
Sverige nu 1977-II
Keywords: consumption; konsumtion; newspaper readership; tidnings läsekrets; periodicals readership; tidskrifts läsekrets; shopping; shopping; holidays abroad; utlandssemestrar; decision making; beslutsfattande; retail outlets; försäljningsställen; domestic appliances; hushållsapparat; consumer goods; konsumtionsvaror; interest (cognitive processes); intresse (kognitiva processer); frequency; frekvens; Consumption and consumer behaviour; Konsumtion och konsumentbeteende; Media; Media; Public relations; Public relations; Social Sciences; Samhällsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap